Pelatihan Pembuatan Media Pembelajaran Interaktif Berbasis Web-Blog Bagi Guru SMP Di Kabupaten Lampung Tengah [Training on Creating Interactive Web-Blog Based Learning Media for Junior High School Teachers in Central Lampung Regency] - Triaristina, Aprilia; Ekwandari, Yustina Sri; Rachmedita, Valensy; Imanita, Myristica (UKInstitute, 2026)
Based on the analysis of the workshop activities in the training on developing interactive learning media using web-blogs for teachers at SMP Negeri 2 Gunung Sugih, the results showed that the average pre-test score of the participants was 58.2, while the average post-test score increased to 75.3. Thus, there was an improvement of 29.4% from the pre-test to the post-test results. This percentage increase indicates that the workshop had a positive impact on enhancing teachers’ competencies in understanding and applying the development of interactive learning media based on web-blogs. Through this activity, teachers gained hands-on experience in developing their creative and technological potential, enabling them to produce more engaging, innovative, and relevant learning media suited to the demands of digital education today. Abstrak: Berdasarkan analisis kegiatan workshop dalam kegiatan pelatihan pembuatan media pembelajaran interaktif berbasis web-blog bagi guru-guru SMP Negeri 2 Gunung Sugih, diperoleh hasil sebagai berikut: nilai rata-rata pre-test peserta pelatihan adalah 58,2 dan rata-rata post-test peserta adalah 75,3. Secara keseluruhan, persentase peningkatan hasil evaluasi peserta dari pre-test ke post-test mengalami peningkatan sebesar 29,4%. Persentase peningkatan ini menunjukkan bahwa workshop dalam kegiatan pelatihan pembuatan media pembelajaran interaktif berbasis web-blog bagi guru-guru SMP Negeri 2 Gunung Sugih sangat bermanfaat. Melalui workshop ini, guru-guru dapat mengembangkan potensinya dalam pembuatan media pembelajaran berbasis web-blog yang menarik dan inovatif.